WHY DO WE NEED THE NOTION OF WILL? - Vogelmann, Rafael (2020)
It is commonly held that the goals at which an action aims are specified by the pro-attitude/belief pairs in light of which the action seems appealing to the agent. I argue that the existence of multiple-incentives cases (i.e., cases in which the agent has more than one incentive to act but in which her motive corresponds to only one of these incentives) shows this thesis to be false. In order to account for such cases we have to ascribe to agents the capacity to actively determine the goals at which their actions aim. I refer to this capacity as the agent’s “will”. Agents endowed with a will are capable not only of determining their own behavior but also their motives. I conclude that the existence of multiple-incentives cases shows that agents have this capacity.